‘–What time is it? –Twenty years past two.’ The role of utilitarian and playful engagement in robot appropriation in later life - Mireia Fernández-Ardèvol; Andrea Rosales; Rebeca Oliván (Archives of Gerontology and Geriatrics Plus)
We analyzed the utilitarian and hedonic (playful) forms of engagement with a socially assistive robot (SAR) by dependent older people in a domestic environment. The case study involved seven users (73–88 years old, five women and two men) living in Barcelona with a certain degree of dependence. Participants hosted the robot in their homes for two months, and their appropriation processes moved between utilitarian (practical) and playful (hedonic) approaches. Practical users expressed a goal-oriented relation with the robot. They were attached to existing interaction scripts, whereas playful users showed comparatively higher levels of experimentation, expressed more entertainment, and perceived more companionship, which positively related to attachment. Playful relationships appear to relate to higher levels of adoption and appropriation of the robot compared to utilitarian ones. The case study demonstrates diverse paths of appropriating a new robotic technology in agentic and varied ways, which helps overcome common stereotypical assumptions that depict (dependent) older individuals as merely passive receivers of such technologies. In terms of design, all participants requested more voice interaction opportunities. Finally, the robot should include personalized hedonic features as playful opportunities to foster adoption.